The Effect Of Work Engagement And Work Stress On Job Satisfaction And Their Impact On Turnover Intention Of Gojek Partners In Jakarta - Lahat, Mohammad Amas; Marthanti, Amas Sari (IJOSMAS, 2021)
The purpose of this study was to analyze the effect of work engagement and job stress on job turnover intention with job satisfaction as an intervening variable. Turnover intentions are a conscious and deliberate willingness to leave the organization, where this phenomenon is interesting to study because the increasing number of turnovers in the company will be detrimental. The influencing factors include Work Engagement, Stress and job satisfaction. This study used 100 selected respondents, namely partners or Gojek drivers around DKI Jakarta. The analysis method uses the Structural Equation Model (SEM) with the SmartPLS 3.0 analysis tool. The results showed that Work Engagement had a positive and significant effect on Job Satisfaction, Work Stress did not significantly affect Job Satisfaction, and Job Satisfaction had a positive and significant effect on Turnover Intentions. Work Engagement has a positive and significant effect on Turnover Intentions, Work Stress does not significantly affect Turnover Intentions, Job satisfaction mediates with a significant variable work engagement on turnover intentions.